2013
DOI: 10.1080/0020739x.2013.822583
|View full text |Cite
|
Sign up to set email alerts
|

Does computer-aided formative assessment improve learning outcomes?

Abstract: Two first-year engineering mathematics courses used computer-aided assessment (CAA) to provide students with opportunities for formative assessment via a series of weekly quizzes. Most students used the assessment until they achieved very high (>90%) quiz scores. Although there is a positive correlation between these quiz marks and the final exam marks, spending time on the CAA component of the course was negatively correlated with final exam performance. Students across the ability spectrum reduced their time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…These results are promising, and coincide with the findings of other research regarding the usefulness of automated FA with regard to student performance and perception [3], [10], [19], [27], [35]. In particular, we agree with Gikandi, Morrow & Davis who, after a meta-analysis in which the review 18 empirical studies, state that such approach can foster a learner focus and enhance student engagement with valuable learning experiences [38].…”
Section: Discussionsupporting
confidence: 90%
“…These results are promising, and coincide with the findings of other research regarding the usefulness of automated FA with regard to student performance and perception [3], [10], [19], [27], [35]. In particular, we agree with Gikandi, Morrow & Davis who, after a meta-analysis in which the review 18 empirical studies, state that such approach can foster a learner focus and enhance student engagement with valuable learning experiences [38].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of improving student learning, Hannah, James and Williams (2014) found that, in their weekly formative online assessments which allowed multiple attempts, some students spent too long perfecting these exercises at the expense of studying higher-level examination-type questions, which Lingard et al (2009, 604) observed are difficult to set in this format. This danger was flagged by Ramsden (1992, 189), when he stated that the "separate assessment of basic skills and knowledge, unless clearly flagged as a relatively unimportant part of the whole assessment process, leads to a focus by students on these activities rather than on more complex ones that are related to understanding."…”
Section: Practical Notes For Implementationmentioning
confidence: 99%
“…Hannah, James, and Williams [8] found that among first year mathematics students, online results in formative assessment tasks correlated well with final examination marks, but this could be mainly a reflection of existing differences in ability and previous studies completed.…”
Section: Comparing Outcomesmentioning
confidence: 96%